2017
DOI: 10.1149/2.1921712jes
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the Degradation Phenomena in Silicon-Graphite Electrodes for Lithium-Ion Batteries

Abstract: Silicon-graphite electrodes usually experience an increase in cycling performance by the addition of graphite, however, the relation of the silicon/graphite ratio and the aging mechanisms of the individual electrode and electrolyte compounds still requires a more fundamental understanding. In this study, we present a comprehensive approach to understand and quantify the degradation phenomena in silicon-graphite electrodes with silicon contents between 20-60 wt%. By evaluating the cycling performance and total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
173
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(203 citation statements)
references
References 52 publications
14
173
1
3
Order By: Relevance
“…Hence, we investigate the use of lithium oxalate as capacity enhancer in combination with silicon/graphite (SiG) electrodes containing 35 wt% nano-Si and 45 wt% graphite. These electrodes, which have been investigated in more detail in a previous study by our group, 25 show a typical first cycle coulombic efficiency of ∼85%. Therefore, we combine them with LNMO cathodes containing 5 wt% lithium oxalate, as the amount of lithium oxalate in these electrodes should largely compensate the irreversible loss during the first cycle.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hence, we investigate the use of lithium oxalate as capacity enhancer in combination with silicon/graphite (SiG) electrodes containing 35 wt% nano-Si and 45 wt% graphite. These electrodes, which have been investigated in more detail in a previous study by our group, 25 show a typical first cycle coulombic efficiency of ∼85%. Therefore, we combine them with LNMO cathodes containing 5 wt% lithium oxalate, as the amount of lithium oxalate in these electrodes should largely compensate the irreversible loss during the first cycle.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have shown that the amount of consumed FEC correlates linearly with the cumulative irreversible discharge capacity (i.e., the sum of the differences between discharge and charge capacity over a certain amount of cycles), 22 which has recently also been demonstrated for SiG anodes with identical composition. 25 Therefore, the cumulative irreversible discharge capacity for each of the analyzed cells is shown on the y-axis of Figure 5, while the amount of consumed FEC in μmol is shown on the lower x-axis. The dashed lines show different e − /FEC ratios, among them the empirically found 4 e − /FEC (= 0.107 mAh irr /μmol) relationship observed by Jung et al 22 The offset of the e − /FEC ratios on the y-axis in Figure 5 can be explained by considering the following: As the lower cell cutoff potential is restricted to 4.0 V, the potential of the SiG anode is limited to a maximum of ∼0.7 V vs. Li/Li + (assuming a maximum cathode potential of 4.7 V vs Li/Li + ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The LiPAA was prepared by diluting a 35 wt% poly(acrylic acid) solution (PAA, MW = 250,000 g mol −1 , Sigma-Aldrich, Germany) with deionized water and neutralizing it with lithium hydroxide (LiOH, Sigma-Aldrich, Germany) to a pH-value of ∼8. 43 The theoretical areal capacity of these electrodes was 1.8-1.9 mAh cm −2 (referenced to the theoretical specific capacities of 3579 mAh g (∼1280 mAh g −1 electrode ) could be utilized at a C-rate of 0.1 h −1 .…”
Section: Methodsmentioning
confidence: 99%
“…By use of scanning transmission electron microscopy (STEM) and energy dispersive spectroscopy (EDS), we investigate the morphology and chemical composition of the silicon particles post mortem after different number of charge-discharge cycles in a SiG//LiFePO 4 pseudo-full cell setup (i.e., with a capacitively largely oversized cathode of ∼3.5 mAh cm −2 ) and a fluoroethylene carbonate (FEC)-based electrolyte. 39 Combining the microscopic characterization with the electrochemical analysis of the cycling stability, the electrode polarization, and the irreversible capacity losses upon cycling allows us to correlate the morphological changes of the silicon particles and the electrode with the observed cycling stability of the SiG electrodes. Electrochemical impedance spectroscopy (EIS) and cross-sectional scanning electron microscopy (SEM) images further complement the discussion by providing additional information about the electrode impedance and the morphological changes of the entire electrode structure as a function of the cycle number.…”
Section: −1mentioning
confidence: 99%